2014
DOI: 10.1523/jneurosci.3437-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

An Unconventional Secretory Pathway Mediates the Cilia Targeting of Peripherin/rds

Abstract: It is unclear how unconventional secretion interplays with conventional secretion for the normal maintenance and renewal of membrane structures. The photoreceptor sensory cilium is recognized for fast membrane renewal, for which rhodopsin and peripherin/rds (P/rds) play critical roles. Here, we provide evidence that P/rds is targeted to the cilia by an unconventional secretion pathway. When expressed in ciliated hTERT-RPE1 human cell line, P/rd is localized to cilia. Cilium trafficking of P/rds was sustained e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 55 publications
6
69
0
Order By: Relevance
“…Using a variety of PRPH2/RDS mutants, pharmacological agents which block protein transport at specific well characterized steps, and high quality fluorescence microscopy in a tissue culture system it was found that PRPH2/RDS could transport to the cilia when trans-Golgi exit was blocked, but does require COPII-mediated exit from the ER. Consistent with a key role for the PRPH2/RDS C-terminal in trafficking, PRPH2/RDS was retained in the cis-Golgi when the C-terminal targeting sequence was eliminated (Tian et al, 2014). Various unconventional secretory pathways have been described (Nickel, 2010; Nickel and Rabouille, 2009), and it is not yet clear which of these is utilized by PRPH2/RDS, however it has been shown that unconventional trafficking of PRPH2/RDS does not require GRASP55 (a known non-conventional secretory protein) (Gee et al, 2011; Tian et al, 2014), and our recent work has suggested that Syntaxin 3 may be involved (Zulliger et al, 2015).…”
Section: Cellular and Molecular Characteristics Of Prph2/rdsmentioning
confidence: 86%
See 1 more Smart Citation
“…Using a variety of PRPH2/RDS mutants, pharmacological agents which block protein transport at specific well characterized steps, and high quality fluorescence microscopy in a tissue culture system it was found that PRPH2/RDS could transport to the cilia when trans-Golgi exit was blocked, but does require COPII-mediated exit from the ER. Consistent with a key role for the PRPH2/RDS C-terminal in trafficking, PRPH2/RDS was retained in the cis-Golgi when the C-terminal targeting sequence was eliminated (Tian et al, 2014). Various unconventional secretory pathways have been described (Nickel, 2010; Nickel and Rabouille, 2009), and it is not yet clear which of these is utilized by PRPH2/RDS, however it has been shown that unconventional trafficking of PRPH2/RDS does not require GRASP55 (a known non-conventional secretory protein) (Gee et al, 2011; Tian et al, 2014), and our recent work has suggested that Syntaxin 3 may be involved (Zulliger et al, 2015).…”
Section: Cellular and Molecular Characteristics Of Prph2/rdsmentioning
confidence: 86%
“…Further support for the idea that PRPH2/RDS traffics to the OS using a specialized transportation mechanism different from other OS components such as rhodopsin came from recent work showing that a large portion of PRPH2/RDS traffics to the OS through a non-conventional secretory pathway which bypasses the trans-Golgi (Tian et al, 2014). Hints that this might be the case had been observed many years earlier when it was discovered that the PRPH2/RDS N-glycan was sensitive to digestion by EndoH, a phenomenon usually associated with failure of a protein to be exposed to the enzyme Golgi mannosidase II in the medial to trans-Golgi (Connell and Molday, 1990; Velasco et al, 1993).…”
Section: Cellular and Molecular Characteristics Of Prph2/rdsmentioning
confidence: 99%
“…In addition, proteins that function in the plasma membrane (e.g., the cGMP channel subunit proteins, such as CNGA1) must be separated from discrete disk membranes (12). ImmunoEM and trafficking studies of PRPH2 have shown that this protein is delivered to the cilium separately from RHO (38), and that it is not included in the most basal disks of rod OS (36,39), consistent with an open lamellar structure for the basal disks. The presence of PRPH2 in the OS coincides only with rim formation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although the complete role of peripherin-2 in this process is not yet fully elucidated, the carboxy-terminal domain of peripherin-2 has been shown to play a role in membrane fusion (Boesze-Battagliaa andStefano 2002, 2003), initiation of rim membrane curvature (Khattree et al 2013), and OS targeting (Tam et al 2004;Tian et al 2014). The D2 loop and covalently linked peripherin-2 complexes are required for the maintenance of the flattened rim morphology (Wrigley et al 2000;Chakraborty et al 2009Chakraborty et al , 2010.…”
Section: The Role Of Peripherin-2 Protein In Photoreceptor Morphogenementioning
confidence: 99%